Vacuum Dressing And Topical Antibacterial Dressing Among Patients With Diabetic Ulcer: A Comparative Study - Tayyab, Syed Muhammad; Ali, Mansab; Usman, Amir; Azeem, Syed Muhammad Mohsin; Ara, Seemab; Rafiq, Tehmina (Biological and Clinical Sciences Research Journal, 2025)
Diabetic foot ulcers (DFUs) represent a significant complication of diabetes mellitus, often leading to prolonged hospitalisation, amputations, and increased morbidity. Effective wound healing strategies are crucial in reducing the burden of diabetic foot ulcers (DFUs), particularly in resource-constrained settings such as Pakistan.AFG Objective: To compare the effectiveness of vacuum-assisted closure (VAC) dressing and topical antibacterial dressing in promoting granulation tissue formation and reducing healing time in patients with diabetic foot ulcers. Methods: A randomised controlled trial was conducted at the Department of General Surgery, University of Lahore Teaching Hospital, from July 2024 to December 2024. A total of 60 patients with clinically diagnosed diabetic foot ulcers were randomly assigned into two groups: Group A received a VAC dressing, while Group B received a topical antibacterial dressing (fusidic acid followed by saline gauze). Outcomes measured included the formation of granulation tissue within two weeks and the duration of complete wound healing. Data were analysed using SPSS version 25. A p-value of less than 0.05 was considered statistically significant. Results: The mean age of participants was 56.2 ± 9.4 years. Granulation tissue formation within two weeks was significantly higher in the VAC group (86.7%) compared to the topical dressing group (60%) (p = 0.018). The mean healing duration was shorter in the VAC group (12.3 ± 3.4 days) than in the topical group (17.6 ± 4.2 days) (p<0.001). Stratified analysis showed significantly better outcomes in patients with higher BMI, poor glycemic control, and non-smokers in the VAC group. Conclusion: VAC dressing significantly enhances granulation tissue formation and reduces healing time in patients with diabetic foot ulcers compared to topical antibacterial dressing. Its implementation in tertiary care hospitals in Pakistan could improve wound healing outcomes and reduce the burden of diabetic complications.